Use of diagnostic modalities for dentofacial imaging in forensic dentistry. Literature review - Castillo Paez, Jose Alberto (2021)
Objective: To describe the use of diagnostic modalities for dentofacial imaging in forensic dentistry. Materials and Methods: A scientific search was carried out in the PubMed, Google Academic, and SciELO databases with the keywords "Dentofacial Imaging", "Panoramic Radiography", "Lateral Cephalogram", "Cone Beam Computed Tomography (CBCT)", "Digital Radiography", and "Forensic Dentistry". Forty-eight recently dated articles published in English were selected, seeking information to describe the use of diagnostic modalities pertaining to dentofacial imaging in forensic dentistry. Results: The most relevant diagnostic modalities of dentofacial imaging for forensic dentistry include panoramic radiography, lateral skull radiography, posterior-anterior skull radiography and cone beam computed tomography. Conclusions: The modalities described, together with morphometric analyses, allow forensic dentists to identify a corpse, estimate age, sex, and even facilitate forensic facial reconstruction for identification purposes.